(untitled) (Journal of Atomic and Molecular Sciences, 2012)
We have applied the grand canonical Monte Carlo method (GCMC) to investigate the physisorption properties of hydrogen storage in BC_3 and carbon nanotubes, respectively. Some important physical amounts under different temperatures and pressures, such as adsorption isotherms and adsorption amounts were studied. The results show that, the physisorption properties of BC_3 nanotube are superior to those of carbon nanotube at all conditions. The main reasons causing such different results between them were analyzed from the interaction energies among nanotubes and H_2 molecules.